Association between cognitive insight and anxiety among community-dwelling schizophrenia patients: the chain mediating effects of family cohesion and chronotype - Dong, Meijun; Wu, Dongmei; Mao, Guoju; Yan, Zhangrong (Frontiers in Psychiatry, 2024)
Objective: To investigate the effect of cognitive insight on anxiety in community-dwelling schizophrenia patients and to construct a chain mediating model to determine the underlying mechanisms of the relationship between cognitive insight and anxiety through family cohesion and chronotype. Methods: The Beck Cognitive Insight Scale, the Chinese version of the Family Adaptability and Cohesion Scale, the Morningness-Eveningness Scale, and the Generalized Anxiety Disorder Scale were used to assess cognitive insight, family cohesion, chronotype, and anxiety in a sample of 785 individuals with schizophrenia living in the community. Spearman correlation analysis, multiple linear regression and Bootstrap methods were employed to analyze the four variables. Results: Residential region, current employment status, and family economic status impacted anxiety among community-dwelling schizophrenia patients. All variables were associated with each other, but self-certainty was not significantly associated with anxiety. Cognitive insight and selfreflection had direct effects on anxiety, as well as indirect effects on anxiety through the partial mediating effect of chronotype, the suppressing effect of family cohesion, and the chain mediating effect of family cohesion and chronotype. Conclusions: Family cohesion and chronotype can mediate the relationship between cognitive insight and anxiety. Improving family functioning, promoting emotional relationships within families, and correcting non-circadian sleep patterns can reduce anxiety in community-dwelling schizophrenia patients, with important implications for improving adverse mental health outcomes.